Questioning the Protection of President’s Dignity in the New Criminal Code - Adi Gunawan; Suhaimi Suhaimi; Adriana Pakendek; Gatot Subroto (IHSA Institute, 2024)
Protecting the president’s dignity in law is not a new thing that has received much controversy from the public, even in the realm of the international state. Even in Indonesia, this article was annulled by the Constitutional Court. Nevertheless, the new Criminal Code has been reinforced, resulting in many pros and cons from the public. Therefore, this research discussed why the article on protecting the president’s dignity was reinserted in the New Criminal Code. This research was normative legal research, while the data source consisted of secondary data, with primary and secondary legal materials such as books, scientific journals, papers, and scientific articles. The data collection process was done through library research using qualitative data analysis. This research used a conceptual approach and studies related to statutory regulations. The research found that protecting the president’s dignity is essential for ordinary people in general. However, in the constitutional realm, a president is an interpretation of the State representing all citizens. Therefore, it is highly justified if this article is reactivated. Apart from that, if this article is not included in the new Criminal Code, it can potentially cause subsociality in public